Users’ Social-interaction Needs While Shopping via Online Sales Configurators - Grosso, Chiara; Forza, Cipriano (International Journal of Industrial Engineering and Management, 2019)
The growing adoption of social web technologies such as social software (SSW) in online configuration environments has enabled the possibility of supporting configurator users in interacting digitally with real people while they are shopping for customizedproducts. Previous research has identified that online sales configurators (OSCs) are currently connected to SSW with different modalities to provide configurator users with a variety of options to digitally interact with real people. Enriching the configuration environment with social-interaction tools has engendered the phenomenon of social-product customization. Recent studies considered the social product-customization by investigating the impact that community feedback and social comparisons has on configurator user. However,theOSCs users’ need to interact with different referentsduring theirconfiguration process, and whether the SSW-OSCs connections respond to this needare still unsearched. To address this gap, the present study explores (a) whether users experience the need to interact with different referents while shopping via OSCs and (b) which interaction modalities users are looking for. By considering 943 configuration experiences from 189 users of 378 OSCs for various consumer goods, the present study finds that the need for social interaction by OSC users is highly relevant. Moreover, OSC users perceive the need to interact with different referents during different stages of the configuration process, and, depending on the referent with whom they wish to interact, they are interested in different interaction modalities in terms of how and where those interactions take place. These findings imply that mass customizers may leverage their customers’ need to interact with real people while shopping online via OSCs in order to better engage their actual and potential customers. Article history: Received (28.10.2018); Revised (15.03.2019); Accepted (6.04.2019)